(untitled) (Journal of Solar Energy Research Updates, 2024)
Abstract: The power output of the photovoltaic (PV) array is nonlinear, and maximum power point tracking (MPPT) is required to boost the efficiency of solar energy generation. The traditional perturb and observe algorithm is frequently used, but it is difficult to comprehensively consider the tracking accuracy and response speed at the same time. Misjudgment occurs when the solar insolation changes drastically. In view of these shortcomings, this paper presents a variable step size threshold search algorithm. The modified algorithm can quickly track the maximum power point and restrain fluctuations near the maximum power point. Matlab is utilized to simulate and prove the effectiveness of this modified algorithm.